2012
DOI: 10.1007/s00192-012-1884-y
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous pushing to prevent postpartum urinary incontinence: a randomized, controlled trial

Abstract: Introduction and hypothesis The risk for urinary incontinence can be 2.6-fold greater in women after pregnancy and childbirth compared with their never-pregnant counterparts, with the incidence increasing with parity. We tested the hypothesis that the incidence of de novo postpartum urinary incontinence in primiparous women is reduced with the use of spontaneous pushing alone or in combination with perineal massage compared with women who experienced traditional directed pushing for second-stage management. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 19 publications
2
35
2
3
Order By: Relevance
“…15 The intervention studied varied between studies: although the control groups always used directed Valsalva pushing, the open-glottis breathing in the intervention group was sometimes spontaneous7–10 12 13 and sometimes directed 56 11 The meta-analysis by Prins et al 14 compared self-directed spontaneous pushing with directed Valsalva pushing (n=425) and concluded that closed-glottis pushing had a negative effect on urodynamic prognosis, consistent with the findings by Schaffer et al 9.…”
Section: Background and Significancesupporting
confidence: 56%
“…15 The intervention studied varied between studies: although the control groups always used directed Valsalva pushing, the open-glottis breathing in the intervention group was sometimes spontaneous7–10 12 13 and sometimes directed 56 11 The meta-analysis by Prins et al 14 compared self-directed spontaneous pushing with directed Valsalva pushing (n=425) and concluded that closed-glottis pushing had a negative effect on urodynamic prognosis, consistent with the findings by Schaffer et al 9.…”
Section: Background and Significancesupporting
confidence: 56%
“…Two meta-analyses [5,6] and seven single-centre, randomised trials reported in nine articles were identified [7][8][9][10][11][12][13][14][15]. Neither participants nor personnel can be blinded to the intervention we consider here.…”
Section: Resultsmentioning
confidence: 99%
“…Lemos pushing [6]. The authors included seven studies [9][10][11][12][13][14][15][16][17], all of which involved potential bias.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study methods for the larger project are reported in detail elsewhere. 26 As an additional component of the parent project, a subset of the participants agreed to allow audio recording of the conversations during the second stage of labor. The audio recordings were intended to serve as a validation of the pushing method used by women during the second stage of labor.…”
Section: Design Setting and Data Collectionmentioning
confidence: 99%